Social Policy in the Legislative Acts of the Government of Stefan Stamboulov (1887-1894) - Sazdov, Dimitar (Research Papers, 2008)
The study reviews the bills passed by the Fifth, Sixth and Seventh People’s Assemblies covering the period of St. Stamboulov’s government. An expanded in-depth analysis focuses on the social provisions of the legislature. Every legislative act is regarded on its own merits as the author attempts to investigate and specify the objective and subjective reasons underlying its adoption as well as incorporating social decisions into its tests.The findings of the study, its conclusions and evaluations of the legislative content correspond to the economic and political development of the country from the Liberation until late ХІХ century. The author has used archives and published documentary materials, periodicals, debates at the People’s Assembly as recorded in shorthand, as well as other research into the problems, etc. These supplementary materials and an insight into the attitudes of different researchers as regards different aspects of Stamboulov’s government enable larger-scale conclusions and assessments of the existing contradictions of the regime. The analysis and the assessments of the social provisions in the legislature of the Fifth, Sixth and Seventh People’s Assemblies enables a multifaceted view of the attitudes and ideas of Stefan Stamboulov as a politician and a statesman.